Role of the 5-HT2C Receptor in Atypical Antipsychotics: Hero or Villain? - Wood, Martyn (Current Medicinal Chemistry - Central Nervous System Agents, 2005)
The atypical antipsychotic drugs (APD) are characterised by an interaction with the 5-hydroxytryptamine (5- HT)2 receptor. Following the identification of the 5-HT2A, 5-HT2B and 5-HT2C receptor subtypes and the development of more selective compounds for these receptors, the role of these receptors in the pharmacological profile of APD has been studied. Although initial interest focussed on the 5-HT2A receptor, recent evidence has suggested that an interaction with the 5-HT2C could be more important. This has been limited by suggestions that 5-HT2C receptor antagonism in APD may be associated with the severe side-effect of weight gain. This review highlights the evidence suggesting that 5-HT2C receptor antagonism could have important benefits in APD profile and that 5-HT2C receptor antagonism does not directly contribute to weight gain.
Keywords: dopamine